Building an Automated win-win Negotiation Process Model - Ghalayini, Latifa; Deeb, Dana (Information Management and Business Review, 2021)
This paper builds an automated negotiation process model for integrative negotiations. The process model defines and automates the necessary phases and activities along with the integrative negotiation approach principles to create win-win outcomes that mutually satisfy negotiating parties. However, to realize this objective, the negotiation literature and theories are reviewed to determine the relevant theories for integrative negotiations that help to develop and form the basis of the process model. After investigation, it became evident that three main theories, which are Decision Theory, Rational Choice Theory and Mutual Gains Theory, contribute to building the integrative process model by setting its phases and components. The model is composed of five main phases with several sub-phases. Decision theory with mutual gains theory provides the robust process model through several phases, and rational choice theory with mutual gains theory ensures they are implemented in a fair, objective manner to come up with a satisfying win-win solution. Hence, automated negotiation processes when designed in a robust manner that is based on the theory that serves integrative approaches could lead to win-win negotiation outcomes. The foundation of the win-win negotiation process model contributes to designing win-win negotiation outcomes through structuring automated negotiation and setting its phases along with the integrative negotiation principles. It develops the negotiation field by integrating automation and the integrative approach principles in a process model.